Smart, Secure, and Energy-Efficient Routing Algorithm for MANETs - Lingaraj, K; Lokesh, KS (International Journal of Computer Sciences and Engineering, 2025)
Energy consumption and security are two critical aspects of Mobile Ad Hoc Networks (MANETs). In MANETs, application security can be ensured through trust management, key management, firewalls, and intrusion detection. Additionally, secure communication is crucial in military applications where urgent and reliable transmission of sensitive information is required. However, most existing routing algorithms do not adequately address both energy efficiency and security in their design. Since these factors are essential for reliable communication in MANETs, it is imperative to incorporate them into routing algorithms. Enhancing security in routing protocols and employing cluster-based routing can significantly reduce energy consumption by preventing security attacks. To address these challenges, we propose a novel secured routing protocol called Cluster-based Energy Efficient Secure Routing Algorithm (CEESRA). This energy-efficient protocol leverages cluster-based routing, where trust scores are used to identify and mitigate intrusions effectively. By integrating intelligent agents for decision-making, CEESRA significantly reduces Denial of Service (DoS) attacks, ensuring a more secure and efficient routing process. Experimental results demonstrate that our proposed trust-based secured routing algorithm not only enhances security but also reduces energy consumption and routing delays, making it a robust solution for MANETs.